Clinical Evaluation of Pulv. Triphala Bhavita Yava and Pulv. Unripe Kadali Phala in Grahani Roga w.s.r to Irritable Bowel Syndrome - Bano, Shabnam; Gupta, HC; Dilawer (International Research Journal of Ayurveda & Yoga, 2022)
Background- Grahani and Agni have Ashraya-Ashrita Sambandha and Paraspara Upakara Bhava (mutually beneficial cycle). So, proper functioning of the element will ultimately boost the proper functioning of the other elements too and of course vis a versa. Grahani and Agni are interdependent, so etiological factors of Agni Dushti can be considered as etiological factors of Grahani Roga. Materials And methods- Clinical trial was carried out in patients of 16-65year of age group having cardinal sign and symptoms of Grahani Roga. Routine Hematological & Biochemical, Stool and Urine investigations were done to rule out any systemic disorder in all the registered patients. Results- It is evident that the trial drug has better results and is significant and highly significant in all subjective parameters In Comparison of all three Groups, Group A showed slight better results in subjective and objective parameters than rest of the two Groups. Conclusion- Mandagni is the root cause of almost all diseases produced in the body (Roga sarve api mandagni). After the detailed study of disease Grahani Roga and clinical work; it may conclude that Mithya Aahara Vihara is the main cause of the Agni dushti, and finally for the disease occurrence. The overall effect of therapies showed that better results observed in Muhurbaddha / Muhurdrava mala pravriti by 77.19% in Group A. In Comparison of all three Groups, Group A showed slight better results in subjective and objective parameters than rest of the two Groups.